2024
DOI: 10.3390/cancers16020410
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Helium Ions’ Potential for Post-Mastectomy Left-Sided Breast Cancer Radiotherapy

Santa Gabriella Bonaccorsi,
Thomas Tessonnier,
Line Hoeltgen
et al.

Abstract: Proton therapy presents a promising modality for treating left-sided breast cancer due to its unique dose distribution. Helium ions provide increased conformality thanks to a reduced lateral scattering. Consequently, the potential clinical benefit of both techniques was explored. An explorative treatment planning study involving ten patients, previously treated with VMAT (Volumetric Modulated Arc Therapy) for 50 Gy in 25 fractions for locally advanced, node-positive breast cancer, was carried out using proton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Yet, helium ions are currently being considered for reintroduction into clinical practice, recognizing their potential benefits over protons and carbon ions [ 11 ]. Indeed, they hold promise in potentially enhancing treatment effectiveness and sparing healthy tissue across diverse tumor sites [ 10 , 12 , 13 , 14 ], potentially further reducing radiation-induced long-term complications. This holds particular significance in the treatment of advanced JNA which are typically localized close to critical structures essential for patients’ quality of life, not least considering the generally young age of the affected patients and their considerable life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, helium ions are currently being considered for reintroduction into clinical practice, recognizing their potential benefits over protons and carbon ions [ 11 ]. Indeed, they hold promise in potentially enhancing treatment effectiveness and sparing healthy tissue across diverse tumor sites [ 10 , 12 , 13 , 14 ], potentially further reducing radiation-induced long-term complications. This holds particular significance in the treatment of advanced JNA which are typically localized close to critical structures essential for patients’ quality of life, not least considering the generally young age of the affected patients and their considerable life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…To date, helium ions are rarely used in clinical settings. Initial studies at the Heidelberg Ion Beam Therapy Center (HIT) showed that helium ion therapy could offer better organs-at-risk sparing compared to protons or conventional photon radiotherapy [17] for head and left-sided breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon therapy is also being considered for rare and hard-to-treat tumors [ 4 ]. Compared to protons and carbon ions, helium ions offer intermediate physical and biological properties [ 6 ], higher relative biological effectiveness and dose-weighted linear energy transfer (LET d ) [ 7 ], and improved lung sparing compared to proton therapy in patients with left-sided breast cancer therapy [ 8 ]. However, while these newer radiation therapies might be better with regard to tumor control, that does not mean that they are necessarily associated with less detrimental effects on the brain or outside the brain.…”
Section: Introductionmentioning
confidence: 99%